1984
DOI: 10.1016/s0006-3495(84)84068-0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cholesterol with galactocerebroside and galactocerebroside-phosphatidylcholine bilayer membranes

Abstract: The interaction of the galactocerebroside, N-palmitoylgalactosylsphingosine (NPGS), with cholesterol has been studied by differential scanning calorimetry (DSC) and x-ray diffraction. Thermal and structural studies demonstrate complex behavior characterized by two endothermic transitions: transition I (TI approximately equal to 50-60 degrees C) corresponding to an NPGS-cholesterol bilayer gel----bilayer liquid crystal transition II (TII where TI less than TII less than TNPGS) corresponding to an NPGS bilayer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 38 publications
(57 reference statements)
4
48
0
Order By: Relevance
“…40 Theoretic and model membrane studies have demonstrated that the systematic addition of cholesterol to biologic membranes can eventually yield such sterol domains. 17,39 -45 At cholesterol levels of Ͼ50 mol % (compared with total phospholipid), an immiscible cholesterol monohydrate phase is formed with a reproducible unit-cell periodicity of 34 Å, in coexistence with the surrounding liquid crystalline lipid bilayer, 43 consistent with that observed in atherosclerotic tissues. This measurement corresponds to a tail-to-tail arrangement of the sterol, as proposed in other model membrane studies using a variety of techniques.…”
Section: Cholesterol As An Important Determinant Of Cell Membrane Strmentioning
confidence: 74%
“…40 Theoretic and model membrane studies have demonstrated that the systematic addition of cholesterol to biologic membranes can eventually yield such sterol domains. 17,39 -45 At cholesterol levels of Ͼ50 mol % (compared with total phospholipid), an immiscible cholesterol monohydrate phase is formed with a reproducible unit-cell periodicity of 34 Å, in coexistence with the surrounding liquid crystalline lipid bilayer, 43 consistent with that observed in atherosclerotic tissues. This measurement corresponds to a tail-to-tail arrangement of the sterol, as proposed in other model membrane studies using a variety of techniques.…”
Section: Cholesterol As An Important Determinant Of Cell Membrane Strmentioning
confidence: 74%
“…7, even in the absence of sterols, CBs formed domains that persist to relatively high temperatures when mixed with 12SLPC. This is not surprising because by themselves CBs exhibit a melting temperature for the ordered (gel) to fluid state transition (up to 80°C) that is much higher than that of SM (33). This is indicative of an inherently stronger tendency of CBs to form domains in a tightly packed state.…”
Section: Effect Of Sterols On Domain Formation By Sm-sterol Effects Omentioning
confidence: 95%
“…Although S o /L d phase coexistence does play a limited role in vivo (30,31), it is nanoscopic L o /L d phase coexistence that is the hallmark of lipid rafts. Ternary lipid mixtures of sphingomyelin, phosphatidylcholine, and cholesterol result in coexisting liquid phases, but nanoscopic fluctuations are expected only close to miscibility critical points (32).…”
Section: Significancementioning
confidence: 99%